2010
DOI: 10.1080/00071660903394455
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal tract morphological alteration by unpleasant physical treatment and modulating role ofLactobacillusin broilers

Abstract: 1. An experiment was conducted to determine the effects of supposedly unpleasant physical treatment on broiler performance, small intestinal development and ameliorating role of probiotics. 2. The following treatments were applied from day one: (1) chicks exposed to normal human contact fed basal diet (control); (2) chicks were exposed to unpleasant physical treatment and fed basal diet (UPT-BD); and (3) chicks were exposed to unpleasant physical treatment and fed basal diet supplemented with Lactobacillus (UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Besides, higher SCFA excretion and increased PYY and PP expression in the NDAPS1 group than the NDS group might be due to an increase in the populations of Lactobacillus spp. 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, higher SCFA excretion and increased PYY and PP expression in the NDAPS1 group than the NDS group might be due to an increase in the populations of Lactobacillus spp. 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of stimulation of Faecalibacterium growth is unclear. In a simulated model of caecal fermentation, the supplementation of certain Lactobacillus strains resulted in similar enhancement (Meimandipour et al, 2010). It was hypothesised that lactate produced by Lactobacillus in the caecal content improved the growth of butyric producers such as Faecalibacterium prausnitzii.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that L. salivarius produces abundant propionate/butyrate (16,17). Additionally, in previous studies, improved barrier function by SCFA was reported (18)(19)(20). SCFAs such as butyrate and acetate are known to protect intestinal barrier integrity by regulating through the activation of AMPK and TLR4.…”
Section: Lactobacillus Salivarius Bp121 Prevents Cisplatin-induced Acmentioning
confidence: 91%